Predicting prognosis using stroke-heart indicator: brain natriuretic peptide in patients with aneurysmal subarachnoid hemorrhage - Xue, Jionghao; Lin, Fa; Liu, Minghao; Song, Wenxiong; Li, Runting; Chen, Yu; Yang, Jun; Han, Heze; Jia, Yitong; Chen, Xiaolin; Wang, Rong; Zhao, Yuanli (Frontiers in Neurology, 2025)
ObjectiveThis study aims to explore the correlation between brain natriuretic peptide (BNP) levels and prognosis in patients suffering from aneurysmal subarachnoid hemorrhage (aSAH).MethodsThis retrospective study included patients diagnosed with aneurysmal subarachnoid hemorrhage (aSAH) at Beijing Tiantan Hospital between January 2015 and September 2021. Plasma BNP levels were measured upon admission and log-transformed to reduce skewness. Elevated BNP was defined as lgBNP ≥1.79 (equivalent to BNP ≥62 pg./mL). The primary outcome was poor prognosis, defined as a modified Rankin Scale (mRS) score ≥ 3 at 90 days. Univariable and multivariable logistic regression analyses were conducted to examine the association between BNP levels and prognosis. Additionally, we assessed the potential impact of incorporating BNP into a predictive model for poor prognosis.ResultsThe statistical analysis encompassed a total of 932 patients. Among them, 171 individuals experienced unfavorable prognosis (mRS ≥3) during follow-up, and 444 patients had elevated BNP levels, defined as lgBNP ≥1.79. After accounting for confounding factors, elevated BNP levels remained a significant independent risk factor of a poor prognosis (p = 0.047, OR = 1.49, 95%CI = 1.01–2.20). Nevertheless, BNP’s predictive value alone might not warrant its inclusion in a prognostic model.ConclusionElevated BNP levels independently forecast unfavorable prognosis in patients with aSAH, even though the cutoff value is lower than the cardiology standards. Continuous monitoring and personalized hospitalization plans can be vital for these patients.